2017
DOI: 10.4028/www.scientific.net/ddf.380.124
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mechanical Properties of Coiled Carbon Nanotubes by Molecular Structural Mechanics Based Finite Element Modelling

Abstract: Carbon nanotubes (NTC) have very spectacular mechanical properties related to their nanometric structure, their perfect arrangement and their one-dimensional geometry. As with all materials, structural defects are inevitable and affects NTC properties. Among these defects, we distinguish the topological defects, the dislocations and the penta-hepta defect. But the presence of these defects is not totally harmful, because the existence of some structure like the coiled nanotube is the result of these defects. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…They also showed that the stretchability of HCNT was in the range of 400–1000%. Some other researches have investigated the mechanical properties of different types of CCNTs. Recently, Zhan et al ,, proposed GH as a new nanoscale spring. This structure is very similar to some types of CCNTs with an ellipsoidal cross-sectional structure.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that the stretchability of HCNT was in the range of 400–1000%. Some other researches have investigated the mechanical properties of different types of CCNTs. Recently, Zhan et al ,, proposed GH as a new nanoscale spring. This structure is very similar to some types of CCNTs with an ellipsoidal cross-sectional structure.…”
Section: Introductionmentioning
confidence: 99%